GENDEN TEDAVİYE YENİ YAKLAŞIMLAR: KODLAMAYAN NÜKLEİK ASİTLER - Hasret Ecevit (Mustafa Kemal Üniversitesi Tıp Dergisi, 2015)
RNA interference (RNAi) also called post transcriptional gene silencing (PTGS), is a biological process in which RNA molecules inhibit gene expression, typically by causing the destruction of specific mRNA molecules. In 2006, Andrew Fire and Craig C. Mello shared the Nobel Prize in Physiology or Medicine for their work on RNA interference in the nematode worm C. elegans, which they published in 1998. It is formed of several different pathways that facilitate gene silencing and negative regulation of expression through non-coding small RNA or RNA particles like small interfering RNA (siRNA), microRNA (miRNA), ribozyme and antisense oligonucleotides. Recently, these small sequences have become a powerful tool for gene silencing in biological studies. The aim of this review is informing the readers about RNAi by explaining the mechanism of molecules which play major role in